Observation of damage initiation for trans-laminar fracture using in situ fast synchrotron x-ray radiography and ex situ x-ray computed tomography - Xu, Xiaodong; Leung, Nathanael; Jargalsaikhan, Urangua; Bongaers, Evi; Sui, Tan (Springer, 2024)
Trans-laminar fracture is an important topic for engineering composites. In this study, trans-laminar fracture initiation in quasi-isotropic carbon/epoxy laminates made of non-crimp fabrics was examined using in situ fast synchrotron X-ray radiography and ex situ X-ray computed tomography. The maximum split lengths were measured by in situ radiography and were compared with the predicted values in a detailed FE model using cohesive elements. Ex situ computed tomography scans were also conducted to confirm that no fibre breakage occurs before the final load drop in the experiments. In situ and ex situ observations are complementary for the understanding of damage initiation.
Keywords: fracture; Fracture toughness; CT analysis; synchrotron X-ray radiography